Mendelian Randomization Analysis Suggests No Associations of Herpes Simplex Virus Infections With Multiple Sclerosis - Zhang, Wan; Wu, Pengfei; Yin, Rui; Sun, Meichen; Zhang, Rongsen; Liao, Xiaoyao; Lin, Yuhong; Lu, Hui (Frontiers in Neuroscience, 2022)
Previous studies have suggested an association between infection with herpes simplex virus (HSV) and liability to multiple sclerosis (MS), but it remains largely unknown whether the effect is causal. We performed a two-sample Mendelian randomization (MR) study to explore the relationship between genetically predicted HSV infection and MS risk. Genetic instrumental variables for diagnosed infections with HSV (p < 5 × 10-6) were retrieved from the FinnGen study, and single nucleotide polymorphisms associated with circulating IgG levels of HSV-1 and HSV-2 and corresponding summary-level statistics of MS were obtained from genome-wide association studies of the European-ancestry. Inverse-variance weighted MR was employed as the primary method and multiple sensitivity analyses were performed. Genetically proxied infection with HSV was not associated with the risk of MS (odds ratio [OR], 0.96; 95% confidence interval [CI], 0.90-1.02; p = 0.22) per one-unit increase in log-OR of herpes viral infections. MR results provided no evidence for the relationship between circulating HSV-1 IgG levels and MS risks (OR = 0.91; 95% CI, 0.81-1.03; p = 0.37), and suggested no causal effect of HSV-2 IgG (OR = 1.04; 95% CI, 0.96–1.13; p = 0.32). Additional sensitivity analyses confirmed the robustness of these null findings. The MR study didn’t support the causal relationship between genetic susceptibly to HSV and MS in the European population. Further studies are still warranted to provide informative knowledge, and triangulating evidence across multiple lines of evidence are necessary to plan interventions for the treatment and prevention of MS.